Recent Progress in Treatment of Pulmonary Fibrosis - Wu, Jieyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Idiopathic pulmonary fibrosis (IPF) is the most common fatal interstitial lung disease.There is no known cause. Its pathogenesis is still unclear, which increases the difficulty of anti-fibrosis drug development. Only two drugs, pirfenidone and Nidanib, are approved for the treatment of IPF, and pharmacological treatments for IPF remain urgently needed.At present, researchers are still working on new drugs to treat idiopathic pulmonary fibrosis.There is an urgent need for drugs to combat pulmonary fibrosis, so researchers are constantly working on new drugs to combat it. This review describes current potential drugs for the treatment of pulmonary fibrosis. The researchers conducted clinical trials to determine the safety and effectiveness of these drugs in patients with pulmonary fibrosis. However, before the trial of some marketed drugs for new indications, the data on adverse reactions, tolerability, physical and chemical parameters, pharmacokinetics and safety have been relatively complete, and researchers have studied the mechanism of action of old drugs, so as to use them for other diseases, the strategy is a useful complement to traditional drug development efforts, offering hope to old, dormant drugs and those on the verge of failure.